TATA KELOLA KECAMATAN KARANGBAHAGIA DALAM MENINGKATKAN PELAYANAN PUBLIK - Tisa Sumaya; Gun Gun Gumilar; Lolita Deby Mahendra Putri (LPPM Universitas Abdurrab, 2026)
Good governance is a reflection of optimal public service quality. Therefore, planned and systematic service managementis an important requirement in improving service quality. With quality human resource management and the application of good governance principles, the government can formulate and implement policies that are more responsive to the needs of the community. Indicators in analyzing governance in services include accountability, transparency, democracy, and the rule of law. This study uses a qualitative design. A case study method was used to understand and explore management in the Karangbahagia subdistrict. Data collection was carried out through observation, interviews, and documentation. Based on the research results, it is known that Karangbahagia Subdistrict has implemented the principles of good governance, especially the principles of accountability, transparency, democracy, and the rule of law. However, in its implementation, it still faces challenges, such as uneven SKM, community participation that does not reach all levels of society, and access to service information that is not easy for some community groups.